The Roles of Landscape Features in Re-Making Sense of Place in Mosul City Centre - Al-Obeidy, Musaab Sami; Shamsuddin, Shuhana (Kurdistan Journal of Applied Research, 2017)
Due to the unfit development of street characteristics, and negligence of maintenance, street loss what is precious and its sense, here the people’s feelings and perception of the streets have been negatively affected. This paper highlights landscape features as physical characteristics of streets including soft landscape (trees) and hard landscape (street furniture). This is to identify the roles of these two types of landscape features in securing sense of place. Nineveh Street in Mosul City Center, Iraq is selected as a case study. Mixed methods were selected for this research, quantitative technique by using 330 questionnaire survey, and qualitative technique by using 30 semi-structured interviews and direct observation. The study concludes that landscape features of streets contribute to create sense of safety and comfort that in turns give sense of place. The lack of the role of landscape features in providing safety and comfort has a negative effect on reducing the influence of sense of place in the street.